FACTORS INFLUENCING COLOSTRUM PROVISION AMONG POST-CESAREAN MOTHERS - Safitri, Ragil Lia; Kristiyanti, Rini (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Colostrum provision is a vital effort in reducing infant mortality, as it contains essential nutrients and antibodies for newborns. However, post-cesarean mothers are at greater risk of delayed or absent breastfeeding initiation due to postoperative discomfort. This study aimed to identify the factors influencing colostrum provision among post-cesarean mothers at RSI Al-Ikhlas Pemalang, focusing on age, education, knowledge, parity, and family support. A quantitative analytical method with a cross-sectional design was employed. Data were collected through structured questionnaires from 66 post-cesarean mothers. Bivariate analysis using the chi-square test revealed that education, knowledge, and family support significantly influenced colostrum provision (p 0.05), whereas age and parity did not show a significant relationship (p 0.05). Furthermore, multivariate analysis using logistic regression identified family support as the most dominant factor affecting colostrum provision. The findings highlight the importance of strengthening educational interventions and fostering family involvement to support early breastfeeding practices in post-cesarean mothers. In conclusion, education, knowledge, and particularly family support plays crucial roles in ensuring the successful provision of colostrum, with family support emerging as the most influential factor. Health professionals are encouraged to engage families as active participants in promoting optimal breastfeeding practices.